Visitors Needs Analysis in Mall XYZ with Text Mining Analysis - Faurizal Limansyah; Mokh. Suef; Vita Ratnasari (IPTEK Journal of Proceedings Series, 2020)
Mall is a shopping center consisting of the main tenants (anchors), retail, shops, services, and public facilities that are built, managed, and arranged by the manager with the aim of conducting interaction between visitors and sellers. In 2018 Surabaya City had 33 malls or 50.77% of the total number of malls in East Java, this shows that the mall population in Surabaya City is very high. Mall XYZ is one of the malls that stood in the city of Surabaya and has been operating for one year. This mall still has not shown a development that is not optimal because of the many complaints from tenants to building management related to the sale of products that do not reach the target, as a result tenants often violate the rules (house rules) that have been set by managers to break the cooperation contract between building management and tenants unilaterally . To find out the cause of these conditions, text mining methods are used to filter reviews from visitors filtered from the Mall XYZ Google page. of the existing reviews classification will be based on reviews that contain positive and negative sentiment. review with positive sentiment becomes an appreciation that must be maintained and improved while a review containing negative sentiment becomes a complaint that must be addressed by the building management as the mall manager.